Customers Perspective in Performance Assessment of Pharmacy Instillation of RSUD X with Balanced Scorecard - Sulistyaningrum, Indriyati Hadi; Satibi, Satibi; Andayani, Tri Murti (Fakultas Kedokteran; Universitas Islam Sultan Agung (UNISSULA), 2013)
Balanced Scorecard performance measurement (financial perspective, customer perspective, internal business perspective, and learning and growth perspective) offers a more thorough and comprehensive evaluation in a public organization such as a hospital. The object of this study was the Department of Pharmacy of RSUD X. This study was descriptive non-experimental. The data were obtained retrospectively and prospectively. The qualitative data were obtained through questionnaires. The quantitative data were obtained through direct observation, surveys. From the research using the Balanced Scorecard data gathering, it has been found that: performance customer perspective showed that the average patient satisfaction was 88% of patients. They were satisfied with the service of the Department of Pharmacy, and the average growth of customers has increased by 10% each month. In conclusions, the working performance of the department of pharmacy was included in a good criteria, with some suggestions and improvements that need to be taken into consideration.